Associations between high-density lipoprotein cholesterol levels and computed tomography-defined low muscle mass in older adults and sex-related differences - Zhang, Weixiao; Liu, Yongkang; Zhang, Yiping; Zhang, Dingzhe; Wang, Jianhua; Chen, Xiao (Frontiers in Endocrinology, 2025)
BackgroundThe associations between high-density lipoprotein cholesterol (HDL-C) levels and the risk of sarcopenia are inconclusive. This study aimed to investigate the association between HDL-C levels and chest computed tomography (CT)-defined low muscle mass in older adults and its sex-related differences.MethodsThis prospective study involved 1995 participants aged ≥50 years. The muscle area of the bilateral erector spinae muscles was measured at the T12 level on a single CT image. Linear regression analysis was used to evaluate the effects of related factors on muscle area. Multivariate logistic regression and restricted cubic spline (RCS) analysis were used to analyze the relationships between HDL-C quartile and low muscle mass in all participants and in the male and female subgroups.ResultsAn increased HDL-C level was associated with a greater risk of lower muscle area overall (β=-1.91, 95% CI: -2.95 to -0.87) and in male participants (β=-3.16, 95% CI: -4.70– -1.61), whereas no significant difference was found in the female subgroup (P > 0.05). A higher continuous HDL-C level was associated with a greater risk of low muscle mass in all participants (odds ratio (OR) =2.28, 95% confidence interval (CI): 1.51–3.45) and in the male subgroup (OR=3.28, 95% CI: 1.84–5.87) after adjustment for confounders, whereas no significant difference was found in the female subgroup (P>0.05). Furthermore, the RCS model showed similar results regarding the relationship between HDL-C levels and the risk of low muscle mass.ConclusionsHigher HDL-C levels were associated with a significantly greater risk of low muscle mass, particularly in older male adults. HDL-C levels are useful in identifying older individuals who are at risk for low muscle mass.